Agricultural Frontiers: Mapping Infrastructure Accessibility and Adaptation in Jammu and Kashmir - Dr. Meenakshi Gupta; Sharma, Dr. Ajay Kumar; Dr. Roop Lal Sharma; Dr Nidhi Yadav (Migration Letters, 2024)
The research explored the farmer’s notions of local level ‘infrastructure’ from across twenty-one districts of Jammu and Kashmir. The study relied on a random sampling approach for the identification of rural areas across twenty-one districts comprising Jammu and Kashmir. The research was conducted in two distinct phases. In the first stage, the farmer’s infrastructure accessibility was assessed, and in the next stage, the farmer’s adaptation tendency was measured. The farmer’s infrastructure availability was accessed with the aid of inputs availability (twelve sub-items), credit availability (four sub-items), information accessibility (twelve sub-items), transport infrastructure accessibility (six sub-items), and post-harvest infrastructure availability at the local level (six sub-items). The farmer’s responses concentrated more in the 34-66 percent interval, signifying medium to moderate accessibility of the agriculture infrastructure facilities in the Jammu and Kashmir region. In terms of scope for adaptability to moderate infrastructure availability, the study undertook the opinion of the farmers with regard to variables: the ability to extend the existing farming contract (Extension Contract), the extent of local-level social participation (Social Participation), the length of farming experience (Farming Experience), and the diversity of income sources (Income-diversity). The regression modelling yielded that adaptation remains a crucial concern across farmer’s mindsets, and getting habitual to low infrastructure availability takes time and seems to be driven by farmer’s perceptions of extension of the existing farming contract, the extent of satisfaction with the current level of income diversity, the extent and depth of social participation, and their respective farming experiences as accumulated over years. Infrastructure accessibility in terms of input availability does seem to shape the real utility of agricultural infrastructure from a farmer’s perspective.